A Glance at Nanjing - Claypool, Lisa (Archīum Ateneo, 2021)
How do we see the places we know best? What does it mean when knowledge of a place does not shape the way we see it but instead bends under the weight of emotions and memories colouring our view? During the 1950s and 1960s, the ink painter Fu Baoshi (1904-65) quietly reflected on these questions in a group of paintings of famous places in his hometown of Nanjing. One of the words the artist used to describe the strange texture and dynamic to his visual encounters with his painting subjects––the “glance” (yipie 一瞥)––is the focus of this short curatorial essay. Fu Baoshi’s “glance” as it is embodied in his landscape paintings challenges academic understanding of the term by revealing its emotional intensity, quality of directness, and, in spite of its heart-beat duration, the way it generates long-lasting impressions. Yet in some respects, the nature of the glance also makes these landscapes hard to see.